Advancing Global Carbon Abatement with a Two-Tier Climate Club - Terrence Iverson (Center for Economic Studies and ifo Institute (CESifo), 2022)
A two-tier climate club exploits the comparative advantage of large countries to mete out punishments through trade, while taking their capacity to resist punishment as a constraint. Countries outside the coalition price carbon at a fixed fraction of the average carbon price adopted within the coalition, or face tariffs. Coalition countries abate more since doing so induces matching abatement elsewhere. If the rate at which noncoalition countries match coalition abatement goes to one, equilibrium abatement approximates the globally efficient outcome even though the coalition only internalizes damages within its borders. Even with a low match rate, the arrangement drastically reduces aggregate abatement costs. In contrast to a single-tier climate club in which many stable coalitions are possible, the stable coalition in the calibrated model is unique and consists of the US and the EU. Global abatement achieved by the stable agreement is about 40 percent of the efficient level.
Keywords: Q54; Q56; Q58; F18; F53; H23; H41; 330; international environmental agreement; climate club; trade sanctions; retaliation; incomplete participation costs; country-size heterogeneity